Identification of critical success factors for the adoption of Industrialized Building System (IBS) in Malaysian construction industry - Saad, S. (Ain Shams University, 2021)
As the global population continues to grow, efficient construction methods without compromising project quality are needed. This study identified the critical success factors (CSFs) required for adoption of Industrialized Building System (IBS) in Malaysian construction industry (MCI). Preliminary factors influencing adoption of IBS from previous studies were contextually adjusted using pilot study. These factors were categorized into five areas: stakeholder understanding, resource availability, process management, issues and perceptions, and future needs. Questionnaires were then administered to 314 IBS players within MCI followed by data analysis methods. Relative Importance Index (RII) ranked increasing skilled labor, introducing renovation capabilities, and removing negative social perception as the main CSFs for adoption of IBS in MCI. The results of this study will be a guide for construction stakeholders to improve efficiency in construction by introducing IBS in MCI. Â© 2021 THE AUTHORS